The importance of browse in late dry season and early wet season diets of cattle and goats in a communal area of the Eastern Transvaal lowveld - Davies, S. J. (My University, 1993)
The contribution of browse and grass to the diets of cattle and goats was assessed in relation to the total biomass of woody foliage and grass available in the study area. Livestock made less use of browse during the dry season than was shown by studies conducted in the Sahel and Nylsvley, northern Transvaal. Goats fed more selectively, utilised newly flushed foliage more and fed upon a greater variety of woody plant species than did cattle. Browse contribute nore to goat diets than to cattle diets although goats were less often supplied with browse. For goats, feeding on standing browse, 'supplied browse and leaf litter occupied 34.7 % of observation time before the tree/shrub flush and 8.3 % post-flush; for cattle the contributions were 14.7 % and 5.8 %, respectively. Fruits, flowers and bark were utilised only during the pre-flush period and only by goats. Goats spent significantly more time grazing and more time browsing than did cattle during the post-flush period. Agave sisalana (sisal) contributed to cattle diets during the preflush and post-flush periods, and to goat diets during the pre-flush period. Since relatively little standing woody foliage is accessible to the animals (16.6 % preflush and 30.7 % post-flush of the wet season maximum), lopping of woody foliage by herders substantially increases the amount of food accessible to livestock, and supplied browse was eaten wherever it was encountered. Aerial cover of grass averaged less than 20 %, grass biomass ,less than 120 kgDM.ha·t and biomass concentration of grass less than 553.5 gDM.m"3 for catena toplands, catena bottomlands and drainage line thickets. The low contribution of browse to livestock diets during this study was due to the scarcity of accessible, palatable forage, exacerbated by the late flush 011 woody plants. In addition, local people harvesting live wood for fuel may compete with foraging livestock. To increase the supply of food for livestock further the rollowing practices could be encouraged: storage of woody foliage litter until the late dry season, use of chemicals to increase the nutritional value of poor quality browse and establishment of woodlots of palatable, perhaps leguminous, evergreen woody species for use as livestock fodder.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg, 1991.
Keywords: Browse--South Africa--Transvaal; Grazing--South Africa--Transvaal; Cattle--Feeding and feeds--South Africa--Transvaal; Goats--Feeding and feeds--South Africa--Transvaal; Forage plants--South Africa--Transvaal